Relation of ferritin levels with symptom ratings and cognitive performance in children with attention deficit–hyperactivity disorder - Oner, Ozgur (2008)
BACKGROUND: The aim of the present paper was to investigate the relationship between behavioral symptoms and attentional and executive functions and hematological variables related to iron deficiency and anemia, ferritin, hemoglobin, mean corpuscular volume (MCV), and red cell distribution width (RDW) in children and adolescents with attention deficit–hyperactivity disorder (ADHD). METHODS: The sample consisted of 52 ADHD children (42 boys, 10 girls; age 7–13 years; mean ± SD, 9.9±2.1 years). Conners Parent and Teacher Rating Scales were obtained. The neuropsychological test battery included Wisconsin Card-Sorting Test (WCST), Stroop, Continuous Performance Test, Digit Symbol and Digit Span subtests of the Wechsler Intelligence Scale for Children Revised (WISC-R), and Trail Making Test A and B, which taps abstraction –flexilibity (WCST), sustained attention (CPT), mental tracking and complex attention (WISC-R Digit Span, Digit Symbol, Trail Making A and B) and interference control (Stroop). Multiple linear regression was used to evaluate the relation of ferritin, hemoglobin, MCV, RDW, age, gender, and presence of comorbidity. RESULTS: While seven children had iron deficiency, none of them was anemic. Lower ferritin levels were associated with higher hyperactivity scores in parental ratings. While performance increased with age for most of the neuropsychological tests utilized, ferritin, hemoglobin, MCV and RDW and gender were not significantly related with cognitive performance in this sample. CONCLUSIONS: At least for the present clinical sample, ferritin levels might be related with behavioral but not cognitive measures in ADHD cases.